Fasilitas Wisata Dan Pengharuhnya Terhadap Minat Berkunjung Kembali Ke Pantai Hunimua, Kabupaten Maluku Tengah - Apner Abdon Elake; Saul Ronad Jacob Saleky; August J. R. Ufie (Jurnal Administrasi Terapan, 2024)
Tourist facilities are one of the determining factors for the interest in revisiting a tourist attraction. The purpose of this study is to determine whether tourist facilities affect the interest in revisiting the Hunimua Beach. This research is a descriptive study. The population in this study includes all visitors to the Hunimua Beach, with a sample size of 70 people. The research results show that the t-test indicates that tourist facilities have a positive and significant impact, demonstrated by the hypothesis testing results with a t-value of 9.903, which is greater than the t-table value of 1.667, with a probability of 0.002 (or <0.05). Thus, the hypothesis proposed in this study is accepted. Based on these research results, it can be concluded that tourist facilities have a positive and significant impact on the interest in revisiting the Hunimua Beach. Keywords: Tourist Facilities, Revisit Intention